Determining Diagnostic Criteria of Unexplained Recurrent Implantation Failure: A Retrospective Study of Two vs Three or More Implantation Failure - Sun, Yingying; Zhang, Yile; Ma, Xueshan; Jia, Weitong; Su, Yingchun (Frontiers in Endocrinology, 2021)
Abstract Background The definition of recurrent implantation failure (RIF) differs clinically, one of the most controversial diagnostic criteria is the number of failed treatment cycles. We tried to investigate whether the two implantation failure could be included in the diagnostic criteria of RIF. Methods A retrospective analysis of the clinical data of patients (N=1518) aged under 40 years with two or more implantation failure, recruited from the Center for Reproductive Medicine of the First Affiliated Hospital of Zhengzhou University from January 2016 to June 2019. Results After adjusting for confounding factors by using binary logistic regression, the results showed that partial general information and distribution of associated factors were significant differences such as maternal age (aOR=1.054, P=0.001), type of cycle (aOR=2.040, P<0.001), stage of embryos development (aOR=0.287, P<0.001), number of embryos transferred (aOR=0.184, P<0.001), female factor (tubal pathology) (aOR=0.432, P=0.031) and male factor (aOR=1.734, P=0.002) between the groups with two and three or more unexplained implantation failure. And further explored whether these differential factors had a significant negative impact on pregnancy outcome, the results showed that: for patients who had three unexplained implantation failure, in the fourth cycle of ET, the live birth rate decreased significantly with age (aOR=0.921, P<0.001), and the live birth rate of blastocyst transfer was significantly higher than that of cleavage embryo transfer (aOR=1.826, P=0.007). At their first assisted pregnancy treatment after the diagnosis of RIF according to these two different definitions, there were no significant difference in the biochemical pregnancy rate, clinical pregnancy rate, ectopic pregnancy rate and abortion rate ( P>0.05), but the live birth rate (35.64% vs 42.95%, P=0.004) was significantly different. According to the definition of ‘two or more failed treatment cycles’, the live birth rate of the first ET treatment after RIF diagnosis was significantly lower than that of patients according to the definition of ‘three or more failed treatment cycles’. Conclusion For patients with unexplained recurrent implantation failure, two implantation failure cannot be included in the diagnostic criteria of RIF. This study supports the generally accepted definition of three or more failed treatment cycles for RIF.